1980
DOI: 10.1083/jcb.86.3.775
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and ultrastructural aspects of Mr 165,000 M-protein in cross-striated chicken muscle.

Abstract: To better understand the relationship between the Mr 165,000 M-line protein (Mprotein) and H-zone structure in skeletal and in cardiac muscle, as well as the possible interaction of M-protein with another skeletal muscle M-line component, the homodimeric creatine kinase isoenzyme composed of two M subunits (MM-CK), we performed biochemical, immunological, and ultrastructural studies on myofibrils extracted by different procedures .In contrast to MM-CK, M-protein could not be completely removed from myofibrils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…This hypothesis is consistent with the perinatal replacement of the EH-splice variant by the more rigid myomesin 1 in heart (Agarkova et al, 2000). While myomesin may be an integral component of myofibrils even in the absence of a structurally visible M-line (Strehler et al, 1980), suggesting that EH-based myofilament linkages might be present in eye muscle, it is not yet clear what adaptive value EH-myomesin 1 may serve in a muscle that lacks the stereotypical structural connections between adjacent myosin filaments. Prior studies Eppenberger et al, 1981;Van der Ven et al, 1999;Yang et al, 2000) have shown that an M-line appears within H-zones of forming myofibrils and that myomesin 1 accumulation is coordinated with that of other myofibrillar proteins.…”
Section: Discussionsupporting
confidence: 49%
“…This hypothesis is consistent with the perinatal replacement of the EH-splice variant by the more rigid myomesin 1 in heart (Agarkova et al, 2000). While myomesin may be an integral component of myofibrils even in the absence of a structurally visible M-line (Strehler et al, 1980), suggesting that EH-based myofilament linkages might be present in eye muscle, it is not yet clear what adaptive value EH-myomesin 1 may serve in a muscle that lacks the stereotypical structural connections between adjacent myosin filaments. Prior studies Eppenberger et al, 1981;Van der Ven et al, 1999;Yang et al, 2000) have shown that an M-line appears within H-zones of forming myofibrils and that myomesin 1 accumulation is coordinated with that of other myofibrillar proteins.…”
Section: Discussionsupporting
confidence: 49%
“…The M-line traverses the center of the A-band and consists of several M-bridges connecting adjacent thick filaments [Luther and Squire, 1978]. Biochemically, three proteins, MM-creatine kinase (43 kD), M-protein (165 kD) and myomesin (185 kD or 190 kD in skeletal muscle or cardiac muscle, respectively) have been identified [Strehler et al, , 1980Grove et al, 1984Grove et al, , 1985. Myomesin is expressed later than ␣-actinin and titin in cultured chicken skeletal myotubes [Lin et al, 1994], but appears at the same time as titin in human fetal skeletal muscle in which the incorporation of M-protein in striated myofibrils occurs later than myomesin [van der Ven and Fü rst, 1997].…”
mentioning
confidence: 99%
“…It is, in fact, of considerable significance, since much of the present biochemical work on characterizing the M-band proteins appears to assume an M-band structure common to all vertebrate muscles. The cryo-sectioning studies which have now been carried out at our laboratories on many different muscles and fibre types from humans, rabbits, chickens, rats, frogs and fish should help to relate the recent plethora of biochemical studies (Trinick & Lowey, 1977;Dhanarajan & Atkinson, 1980;Mani et al, 1980;Strehler et al, 1980) to the specific M-band structure (or structures) known to be present in the particular muscles involved. It is a mistake to assume that A-band structure in all vertebrate muscles is the same.…”
Section: Cryo-sections and Vertebrate Muscle Researchmentioning
confidence: 99%